Free vibration analysis of rectangular plates with exponentially varying thickness - Tutak, Bulent; Aksu, Guven (ASME, 1996)
The free transverse vibration characteristics of rectangular plates, including the effect of transverse shear deformation and rotary inertia, are presented. A method based on the variational procedure in conjunction with the finite difference technique is used to determine the natural frequencies and mode shapes. The convergence characteristics of the present method are studied by varying the thickness parameter. The effects of the thickness parameter and taper thickness ratio on the variation characteristics are studied.
Proceedings of the 1996 3rd Biennial Joint Conference on Engineering Systems Design and Analysis, ESDA. Part 7 (of 9) -- 1 July 1996 through 4 July 1996 -- Montpellier, Fr -- 46123
Keywords: Convergence of numerical methods; Finite difference method; Natural frequencies; Plates (structural components); Shear deformation; Variational techniques; Rotary inertia; Taper thickness ratio; Thickness parameter; Vibrations (mechanical)